Surgical Management of Dystocia Due to Uterine Torsion in a Persian Cat - Yadav, Lakshmi; Singh Gurjar, Kuldeep; Purohit, Shivani (The Indian Journal of Animal Reproduction, 2025)
A female Persian cat having four years of age was presented with history of fifty eight days of gestation, anorexia, vaginal discharge and abdominal distension at Veterinary Clinical Complex, PGIVER Jaipur. The female cat had delivered three dead fetus, showing crying behavior. Radiography revealed presence of three underdeveloped fetus and ultrasonography was performed which showed no cardiac activity. An emergency caesarean section was performed which discovered uterine torsion of 360° in right horn. Thereafter, an ovariohysterectomy was performed as the uterus was necrosed under general anaesthesia. After receiving fluid therapy and antibiotics, the patient recovered and regained appetite a few days after the surgery.